Capa - Sumário - Apresentação - Lima, Náthalee Cavalcanti Almeida; Terrematte, Patrick Cesar Alves; Rique, Thiago Pereira (Anais do Encontro de Computação do Oeste Potiguar ECOP/UFERSA (ISSN 2526-7574), 2017)
Capa - Sumário - Apresentação